Linking Endotoxins, African Dust PM10 and Asthma in an Urban and Rural Environment of Puerto Rico - Mario G. Ortiz-Martínez; Rosa I. Rodríguez-Cotto; Mónica A. Ortiz-Rivera; Cedric W. Pluguez-Turull; Braulio D. Jiménez-Vélez (Mediators of Inflammation)
African Dust Events (ADE) are a seasonal phenomenon that has been suggested to exacerbate respiratory and proinflammatory diseases in Puerto Rico (PR). Increases in PM10 concentration and the effects of biological endotoxins (ENX) are critical factors to consider during these storms. ENX promote proinflammatory responses in lungs of susceptible individuals through activation of the Toll-like receptors (TLR2/4) signaling pathways. The objective of the study was to evaluate the toxicological and proinflammatory responses stimulated by ADE PM10 ENX reaching PR using human bronchial epithelial cells. PM10 organic extracts from a rural and urban site in PR (March 2004) were obtained from ADE and non-ADE and compared. A retrospective data analysis (PM10 concentration, aerosol images, and pediatric asthma claims) was performed from 2000 to 2012 with particular emphasis in 2004 to classify PM samples. Urban extracts were highly toxic, proinflammatory (IL-6/IL-8 secretion), and induced higher TLR4 expression and NF-κB activation compared to rural extracts. ENX were found to contribute to cytotoxicity and inflammatory responses provoked by urban ADE PM10 exposure suggesting a synergistic potency of local and natural ENX incoming from ADE. The contribution of ADE PM10 ENX is valuable in order to understand interactions and action mechanisms of airborne pollutants as asthma triggers in PR.